2011
DOI: 10.1227/neu.0b013e318208f360
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of Ventricular Cerebrospinal Fluid Shunt Surgery in Adults: An 8-Year Study

Abstract: Shunt surgery still carries a high morbidity rate, with a mean of 2.2 reoperations per patient in 23.3% of patients. Our risk-factor data suggest methods for decreasing shunt-related morbidity, including peritoneal routing whenever possible and special attention to preventing CSF leaks after craniotomy or external ventriculostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 29 publications
7
112
0
8
Order By: Relevance
“…Mechan ical dysfunction remains the most common cause of this failure. 5 The most common reason for proximal catheter failure is believed to be obstruction of the catheter by the choroid plexus; 10 theoretically, optimal catheter placement should help reduce this risk. In pediatric patients, this fac tor has been examined by comparing endoscopically ver sus nonendoscopically placed ventricular catheters.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…Mechan ical dysfunction remains the most common cause of this failure. 5 The most common reason for proximal catheter failure is believed to be obstruction of the catheter by the choroid plexus; 10 theoretically, optimal catheter placement should help reduce this risk. In pediatric patients, this fac tor has been examined by comparing endoscopically ver sus nonendoscopically placed ventricular catheters.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…However, the advantage of our study was that all patients were managed in highly standardized conditions 36,37 that allowed us to identify clinically relevant independent risk factors. Nevertheless, a prospective and multicenter study featuring different intensive care unit therapeutic strategies should be conducted to confirm the value of this improved score.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Total shunt revision in our series represented 58.1% of shunt procedures which is much higher than the result of Naftel et Shunt-related infections represent 2 to 27% of total shunt procedures (8,15,18,21,22,28,27,30). Shunt revision due to shunt related infection in our study represented 11.22% of the total cases which is slightly higher than the result of Kulkarni et al (26) who reported 10% infection rate after VPS insertion but less than the results of Kinasha et al (13) who reported 24.6% shunt related infection but overall in our elective neurosurgical procedures the incidence of shunt related infection is still accepted.…”
Section: Discussionmentioning
confidence: 53%